Comprehensive insights into areca nut: active components and omics technologies for bioactivity evaluation and quality control - Sun, Yuanyuan; Feng, Jian; Hou, Wencheng; Qi, Huasha; Liu, Yangyang (Frontiers in Pharmacology, 2024)
Areca nut (AN), the fruit or seed of Areca catechu Linn, has many uses, including chewing and medicinal purposes. It has sparked worries about health due to the presence of alkaloids. Chewing AN may have a variety of negative consequences; however, the medicinal use of AN has no notable adverse effects. To completely understand and effectively use AN, researchers have investigated its chemical makeup or biological activity, analyzed the variations between different AN species and different periods, and improved extraction and processing procedures. Today, an increasing number of researchers are exploring the underlying reasons for AN variations, as well as the molecular mechanisms of biosynthesis of chemical components, to comprehend and change AN at the genetic level. This review presents an overview of the clinical study, pharmacology, and detection of the main bioactive components in AN, and the main factors influencing their content, delving into the omics applications in AN research. On the basis of the discussions and summaries, this review identifies current research gaps and proposes future directions for investigation.